4-(5+x)=3

Simple and best practice solution for 4-(5+x)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-(5+x)=3 equation:


Simplifying
4 + -1(5 + x) = 3
4 + (5 * -1 + x * -1) = 3
4 + (-5 + -1x) = 3

Combine like terms: 4 + -5 = -1
-1 + -1x = 3

Solving
-1 + -1x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -1x = 3 + 1

Combine like terms: -1 + 1 = 0
0 + -1x = 3 + 1
-1x = 3 + 1

Combine like terms: 3 + 1 = 4
-1x = 4

Divide each side by '-1'.
x = -4

Simplifying
x = -4

See similar equations:

| -3(x-2)+3x=-6 | | 1000000009+3009000= | | 2x-20-64=0 | | 4(2-3b)=62 | | 9u+4=19 | | y^2-y-132=0 | | g(x)=log(x-5) | | 8R-2=2R+6-4R | | 8x-(2x+6)=24 | | 9x^2+18y^4= | | 66*8= | | 32b^2+12b= | | 3u+(u-2)=10 | | y^2-10y=-23 | | (x-2)5=0 | | (x-2)5=x | | 6a^3+15a= | | 5x+3y=-8 | | 5r^2-26r=24 | | 4b^2-17b=15 | | 18.3x-7.6=8.4x-14.6 | | 3t^2-13t-16=0 | | (2x+1)(x-4)(3x+5)=0 | | 5x-2(x-2)=11 | | -8x+20+10x=42 | | 3x-7=9+7x | | x+8=-2-x | | 15x^2+2xy-8y^2=0 | | 80x=-280 | | 100x=400 | | 2(x+2)=3(3x-4) | | 23x+10=28x+30 |

Equations solver categories